Physical Therapists' Assessment of Patient Self-Efficacy for Home Exercise Programs - Kelsey J Picha; Alison Snyder Valier; Nicholas R Heebner; John P Abt; Ellen L Usher; Gilson Capilouto; Tim L Uhl (North American Sports Medicine Institute, 2021)
# Background Patient adherence to home exercise programs (HEPs) is low, and poor patient self-efficacy is a barrier clinicians can influence. However, little evidence suggests that clinicians assess level of patient self-efficacy before prescribing HEPs. # Purpose To determine the importance of patient self-efficacy to physical therapists (PTs) when addressing patient barriers, determine how PTs assess and use patient self-efficacy for HEPs, and describe the barriers facing PTs when assessing patient self-efficacy for HEPs. # Study Design Survey. # Methods Practicing PTs were recruited from the American Physical Therapy Association's Orthopedic Section and emailed the electronic survey. # Results Email invitations were sent to 17730 potential participants, and 462 PTs completed the survey over one month. PTs rated self-efficacy as "very" to "extremely" important for patient adherence (58%, 265/454). Most (71%, 328/462) reported assessing self-efficacy before prescribing HEPs and did so through verbal discussion and observation of the patient (50% and 38% respectively). Half of respondents individualized HEPs through self-efficacy related themes. PTs not assessing self-efficacy reported not knowing how (51%, 68/134), being unsure what to do with the information (24%, 32/134), or reporting other barriers (21%, 28/134). # Conclusions Most PTs indicated that self-efficacy was important for patient adherence, but assessment strategies reported, such as verbal discussion and observation, may not be the most accurate. PTs who did not assess self-efficacy reported not knowing how or what to do with the information once collected. These findings suggest that there is a gap in knowledge related to how to evaluate self-efficacy for HEPs. Better assessment of self-efficacy may lead to more appropriate and effective implementation strategies. # Level of Evidence Level II